Tactical Psychology in Operation Veritable - Rooney, Dermot (Cranfield University, 2020)
Research into tactical psychology has found remarkable effects on opponent willingness and ability to fight from applying apparently simple techniques. Combining threats causes indecision and inaction, more than doubling the number of opponents surrendering. Flanking give an obvious sign that the opponents are unlikely to succeed and more than trebles the number withdrawing from combat. Proximity -getting close to the enemy- once the first two effects are achieved, allows interpersonal non-verbal negotiation which ‘seals the deal’. This rapidly ends the engagement in favour of the attacker (Rooney, Bennett and Salt, 2018). However, these findings are merely indicative, being based on small opportunity samples using assessment techniques that do not account for operational and strategic level effects. This PhD study is examining over 100 armed engagements from a single operation to apply robust statistical tests to more reliable and valid measures. The findings will provide a clearer picture of the effects of tactical psychology and the obstacles to applying it, informing UK tactical doctrine and collective training to greatly increase operational effectiveness.
Keywords: 'Tactical'; 'Psychology'; 'Veritable'; 'DSDS19'; 'DSDS19 Poster'; 'Psychology not elsewhere classified'